Improving the Mathematical Representation and Self Confidence through Realistic Mathematics Education Approach for Junior High School - Nani Suryani; M. Ikhsan; Marwan Marwan (Proceedings of AICS - Social Sciences, 2018)
Mathematical representation ability is one of the skills that students need to have in the 2013 curriculum learning and self-confidence is one of the psychological aspects that students need to have in the 2013 curriculum learning. The low ability of mathematical representation and confidence of students shows the need for improvement efforts in the implementation of mathematics learning, these efforts made by applying the approach of Realistic Mathematics Education. The purpose of this study was to determine the increase in the ability of mathematical representation and self-confidence of students through a realistic mathematics education approach. The type of this research is experimental research with quantitative approach. The research design used in this research is True Experimental Design with pre-test and post-test control group design. The population in this study were all students of class VII Junior High School, with two class samples of class VII-4 as the experimental class and class VII-5 as control class obtained by random sampling. The research instrument used was a mathematical representation ability test and a student confidence questionnaire — data analysis performed by finding N-Gain value, normality test, homogeneity test, and t-test based on students' initial and final ability. The results showed that there was an increase in the ability of mathematical representation and self-confidence of students through a realistic mathematics education approach.Keywords: ability of mathematical representation, self-confidence, realistic mathematics education approach.